(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
The research was conducted for the assessment of genetic diversity using both morphological and random amplified polymorphic DNA (RAPD) analysis of twelve guava (Psidium guajava L.) varieties growing in Bangladesh. Morphological characterization of guava varieties showed a wide range of variation. The highest variability was observed between Poly and Jelly varieties.Polymerase chain reaction with 5 arbitrary 10-mer and 3 arbitrary 12- mer RAPD primers produced a total of 50 bands of which 75.23 percent were polymorphic. The highest percentage of polymorphic loci (100%) was observed for primer A and the lowest (50%) for A03 primer. The UPGMA dendrogram revealed the segregation pattern and the difference of evolutionary changes. Guava varieties were separated into two main groups, one of them was made up of Chineese, Jelly, Kazi, Apple, L-49, Local-2 and Local-3. The other one was made up of Local-1, Poly, Kashi, Thai and Bombay. The highest genetic distance between Apple and Kazi peyara indicate that these varieties might be interesting in breeding programme for improving trait of interest. This scientific information could be used for further improvement of guava. Jahangirnagar University J. Biol. Sci. 7(2): 89-98, 2018 (December)